2020
DOI: 10.1093/bib/bbaa168
|View full text |Cite
|
Sign up to set email alerts
|

The Cellular basis of loss of smell in 2019-nCoV-infected individuals

Abstract: A prominent clinical symptom of 2019-novel coronavirus (nCoV) infection is hyposmia/anosmia (decrease or loss of sense of smell), along with general symptoms such as fatigue, shortness of breath, fever and cough. The identity of the cell lineages that underpin the infection-associated loss of olfaction could be critical for the clinical management of 2019-nCoV-infected individuals. Recent research has confirmed the role of angiotensin-converting enzyme 2 (ACE2) and transmembrane protease serine 2 (TMPRSS2) as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 67 publications
0
53
0
2
Order By: Relevance
“…To assess whether olfactory receptor neurons may be susceptible to infection by SARS-CoV-2, investigators have determined which cell types in the olfactory epithelium express the obligatory entry proteins for the new coronavirus, angiotensin-converting enzyme 2 (ACE2) and transmembrane protease, serine 2 (TMPRSS2). These gene and protein expression studies were performed by RNAseq of identified cell types, or using markers for distinct cell types within the olfactory epithelium combined with gene or protein expression for ACE2 and TMPRSS2 [ 6 , 8 , 11 , 23 , 38 , 42 , 52 , 66 , 98 , 103 , 106 ]. The large majority of these studies concluded that sustentacular cells (the primary support cells in the olfactory epithelium) and cells in Bowman’s glands express the virus entry proteins, while all human studies and the majority of animal studies reported that olfactory receptor neurons do not express ACE2, or express ACE2 only very rarely (Tables 1 , 2 and 3 ).…”
Section: Can Olfactory Neurons Become Infected By Sars-cov-2?mentioning
confidence: 99%
“…To assess whether olfactory receptor neurons may be susceptible to infection by SARS-CoV-2, investigators have determined which cell types in the olfactory epithelium express the obligatory entry proteins for the new coronavirus, angiotensin-converting enzyme 2 (ACE2) and transmembrane protease, serine 2 (TMPRSS2). These gene and protein expression studies were performed by RNAseq of identified cell types, or using markers for distinct cell types within the olfactory epithelium combined with gene or protein expression for ACE2 and TMPRSS2 [ 6 , 8 , 11 , 23 , 38 , 42 , 52 , 66 , 98 , 103 , 106 ]. The large majority of these studies concluded that sustentacular cells (the primary support cells in the olfactory epithelium) and cells in Bowman’s glands express the virus entry proteins, while all human studies and the majority of animal studies reported that olfactory receptor neurons do not express ACE2, or express ACE2 only very rarely (Tables 1 , 2 and 3 ).…”
Section: Can Olfactory Neurons Become Infected By Sars-cov-2?mentioning
confidence: 99%
“…OSNs project directly to the OB, and thus provide an entry route for pathogens to the brain (reviewed in Dando et al, 2014). Cells in the OE can themselves be damaged by viral infection, leading to a reduction, change, or loss of sense of smell (Brann et al, 2020;Gupta et al, 2020;Kraus et al, 2020). The identification of zebrafish olfactory rod cells, with their unique flexible actin-rich protrusion, offers new opportunities to explore the biology of these cells in a genetically tractable model organism, and thus to understand their contribution to the multimodal sensory functions of the vertebrate olfactory epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…OSNs project directly to the OB, and thus provide an entry route for pathogens to the brain (reviewed in [Dando et al, 2014]). Cells in the OE can themselves be damaged by viral infection, leading to a reduction, change, or loss of sense of smell, a phenomenon that has attracted much recent attention due to the damaging action of SARS-CoV-2 on the human olfactory system (Brann et al, 2020; Gupta et al, 2020). In the zebrafish, new functions of the OE, such as the detection of sodium and chloride ions (Herrera et al, 2020), continue to be uncovered.…”
Section: Discussionmentioning
confidence: 99%